Pattern of Macro benthos Succession in Sabang Waters after Tsunami - Rudi, Edi; Fadli, Nur (Biospecies, 2009)
Research about succession of macro benthos on limestone substrate was conducted atthree sites (Klah Island, Gapang Beach and Gapang Mangrove) in the coral reef ecosystem of WehIsland from April – December 2005. The selections of the sites are based on degradation of watersquality and coral reef condition. Limestone substrate as collectors were laid at 5 m waters depth ateach site, and further were taken after four and eight months. Succession pattern of macro benthoswas analyzed by Frontier Succession curve. The result shows that pattern of macro benthossuccessions were occurred significantly between locations and time. At site poor of natural coral reefcondition (Gapang Mangrove), succession pattern is in disturbance condition, while in Gapang Beachand Klah Island and Pulau Payung, which have good and fair coral condition, succession patterns aregoing in the direction of equilibrium condition. The result has indicated that waters quality is key factorfor macro benthos succession